2021
DOI: 10.1186/s13063-020-04963-2
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal effect of povidone iodine on COVID-19 in the nasopharynx: A structured summary of a study protocol for an open-label randomized clinical trial

Abstract: Objective General: To assess the virucidal efficacy of povidone iodine (PVP-I) on COVID-19 virus located in the nasopharynx Specific: i. To evaluate the efficacy of povidone iodine (PVP-I) to removeCOVID-19 virus located in the nasopharynx ii. To assess the adverse events of PVP-I Trial design This is a single-center, open-label randomized clinical trial with a 7-arm parallel-group design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…The virucidal effect of PVP-I on COVID-19 replication in the nasopharynx has been reported in other studies such as [23] [24].…”
supporting
confidence: 66%
“…The virucidal effect of PVP-I on COVID-19 replication in the nasopharynx has been reported in other studies such as [23] [24].…”
supporting
confidence: 66%
“…The authors followed the Extension of the Consolidated Standards of Reporting Trials (CONSORT) 2010 guideline [ 3 ]. The study protocol was published elsewhere [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering the effect of NVL on the course of the disease, various experiences were presented in order to provide local control. The effectiveness of PVP–I mixtures prepared in different forms, nasal spray, gargle and mouthwash, and at different concentrations, 0.4%, 0.5%, 0.6% and 1% against SARS‐CoV‐2 has been demonstrated by various studies 7,21,22 . These studies indicated that PVP–I reduced the viral load of SARS‐CoV‐2 by showing a virucidal effect, and PVP–I solutions were defined as an effective method of reducing the viral load of SARS‐CoV‐2 23,24 .…”
Section: Discussionmentioning
confidence: 99%